INFANTILE MORTALITY DUE TO CONGENITAL CARDIOPATHIES IN A PERIOD OF NINE YEARS IN VILLA CLARA - Maribel Navarro Ruiz; Manuela Herrera Martínez (Medicentro, 2013)
Introduction: Congenital cardiopathies constitute one of the first causes of infantile mortality in Villa Clara. Objective: To characterize, from the epidemiological and clinical point of view, infantile mortality due to congenital cardiopathies diagnosed in neonatal stage. Methods: An epidemiological, clinical and descriptive study was performed in the Neonatology service of the University Hospital “Mariana Grajales” during nine years (2000-2008). The sample was integrated by 249 neonates with the diagnosis of congenital cardiopathy before 28 days, who were improving until first year of life. A survey was made and variables were controlled. A database was also made and information was processed statistically. Results: Infantile mortality rate due to congenital cardiopathy diagnosed during neonatal stage was of 0, 75 for each thousand born alive. Infantile mortality due to congenital cardiopathy showed an improvement in the last years. The 100 % of the infants with coarctation of the aorta died. The 66,1 % of the deceased infants showed other complications. In operated neonates, more than 55 % remained alive after first year. The diminution of neonates´deads with cardiopathies is thanks to the experience of the neonatology staff and the smooth running of cardiopediatric network. The presence of complex congenital cardiopathies, and their complications, were frequent, in spite of infants were or were not operated on surgically. Conclusions: The most congenital cardiac defects, like cause of death, showed important hemodynamics, clinical, and anatomical complexity.